Hypophosphatasia - Schlesinger, Bernard (The Turkish Journal of Pediatrics, 1958)
Here then is another disorder in which hypercalcaemia is the most prominent biochemical result. It carries with it the risk of renal damage, which may at times prove fatal. The disease must be differentiated from rickets, congenital syphilis and hyperparathyroidism, but there is plenty of clinical and pathological evidence to exclude all these. It is an example of an hereditary disorder, confirmed by discovering grossly abnormal amounts of phosphorylethanolamine in the urine on chromatography. Beyond finding a persistently low alkaline phosphatase in the blood and many of the tissues, the pathogenesis is unknown and there is no known specific treatment.